Assesment the efficiency of some local fungal isolates in the production of Laccase enzyme - Ghaidaa S. Hussein; Walla H. Shuker; Israa N.Lateef (Al-Qadisiyah Journal of Pure Science, 2019)
In this study (34) samples of fungal from infected fruits and vegetables were isolated related to the following species:Alternariaalternata,Aspergillusflavus,A. niger,Fusarium sp. and Penicillium sp. Their ability to produce Laccase enzyme was studied and the study showed the ability of (11) fungal isolates to produce this enzyme and the A. alternata is the strongest one to produce the Laccase enzyme reaching (1.35 U/ml). Optimization of some nutritional and physical factors in the basal medium in order to intensify the production from A. alternata. The optimization studies revealed that the maximum Laccase production was achieved when the production medium was at the following conditions: pH 5.5 sucrose as a carbon source, yeast extract as nitrogen source was (4.01 u/ ml).